Clinical Presentations and Species Spectrum of Nontuberculous Mycobacteria in Suspected Pulmonary Tuberculosis Cases - Sivasankar Das; Prasanta Raghab Mohapatra; Sutapa Rath; Sourin Bhuniya; Baijayantimala Mishra (Journal of Global Infectious Diseases, 2025)
Introduction: The prevalence of nontuberculous mycobacteria (NTM) is on the rise worldwide. The diagnosis of NTM lung disease (NTM-LD) is a dilemma. The 2020 guidelines jointly established by the American Thoracic Society (ATS) and Infectious Diseases Society of America (IDSA) outline the criteria for diagnosing pulmonary NTM disease. Herein, we report a series of cases with an analysis of relevant literature to gain insight into the pathogenicity of NTM species, the risk factors involved, and treatment strategies. Methods: This is a prospective observational study starting from April 2023 to December 2023. A total of 370 suspected pulmonary tuberculosis (TB) patients were included. Clinical specimens were processed for Ziehl–Neelsen staining, GeneXpert Mycobacterium tuberculosis (MTB)/RIF assay, and culture. Culture-positive mycobacteria were classified as MTB complex or NTM based on detection of MPT64 antigen. The NTM isolates were speciated by line probe assay using GenoType® Mycobacterium common mycobacteria (Hain Lifescience, Nehren, Germany). The criteria of ATS/IDSA were applied to confirm NTM-LD. Results: Nine (n = 9) patients were diagnosed as cases of NTM-LD. Bronchiectasis and previous TB were the most common comorbidities. Mycobacterium scrofulaceum (n = 2), Mycobacterium szulgai (n = 2), Mycobacterium intracellulare (n = 1), Mycobacterium kansasii (n = 1), Mycobacterium abscessus (n = 1), Mycobacterium fortuitum (n = 1), and Mycobacterium interjectum (n = 1) were the species involved. Specific therapeutic drug regimens were administered in four cases, which resulted in clinical improvement. Conclusion: People with comorbid (LDs) are at risk of NTM-LD. The severity of NTM-LD and mortality also depend on the species involved. New guidelines with evidence-based recommendations should be formulated to simplify the diagnosis and treatment of NTM-LD caused by an array of more than 190 species.